Modelling triple diffusion of 63Ni in UFG Cu–Zr ingots. (August 2021) - Lappas, K.I.T.; Konstantinidis, A.A.; Aifantis, E.C.
Abstract: The main purpose of this work is to provide a theoretical interpretation of specific diffusion profile data found in the literature, by employing a "triple diffusion" model. We extend Aifantis' "double diffusivity" model to diffusion in media containing three families of diffusion paths, each one having a different diffusion coefficient. We suggest that the approach proposed herein may also be applicable to revisit some categories of diffusion profile measurements, earlier addressed with single or double diffusion formulations. Grain boundary (GB) diffusion experiments in severely deformed materials under specific conditions are most relevant for applying the triple diffusivity framework. Such materials have complicated microstructures which include more than two diffusion paths and, under specific conditions, their concentration profiles might show three distinct slopes. Graphical abstract: Modelling triple diffusion data of 63Ni in UFG Cu – Zr ingots in various temperatures Image, graphical abstract